Optimizing protocols for monitoring in vivo replication of a novel chimeric Marek’s Disease vaccine with an insertion of the Long Terminal Repeat of Reticuloendotheliosis Virus in the CVI988 Strain genome (CVI-LTR) - Faiz, Nik M.; Cortes, Aneg L.; Phang, Yuen-fun; Gimeno, Isabel M. (Taylor and Francis, 2024)
Monitoring Marek's disease (MD) vaccination is routinely done by evaluating the load of MD vaccine in the feather pulp (FP) between 7 and 10 days of age. However, attempts in our laboratory to detect a novel CVI-LTR vaccine in the FP samples from commercial flocks failed. The objective of this study was to evaluate the most suitable tissue and age to monitor CVI-LTR vaccination. We used two different commercial CVI988 vaccines as controls. One hundred and sixty 1-day-old commercial brown layers were vaccinated with either CVI-LTR, CVI988-A, CVI988-B or remained unvaccinated. Samples of the spleen, thymus, and bursa were collected at 3, 4, 5, and 6 days of age and samples of FP were collected at 7 and 21 days for DNA isolation. Our results showed that CVI-LTR replicated earlier than CVI988 vaccines in the lymphoid organs but was not detected in the FP at either 7 or at 21 days of age. We also confirmed that either the spleen or thymus collected at 4-6 days was a suitable sample to monitor CVI-LTR vaccination in commercial flocks. Finally, we evaluated the load of oncogenic MDV DNA in five commercial flocks that were vaccinated with either CVI-LTR + rHVT or CVI988-A + rHVT. The load of oncogenic MDV DNA was evaluated at 21 days in the FP in 20 chickens per group. Our results demonstrated that CVI-LTR was more successful in reducing oncogenic MDV DNA at 21 days of age than the CVI988-A strain.RESEARCH HIGHLIGHTSCVI-LTR replicates in the thymus and spleen earlier than CVI988.CVI-LTR replicates in lymphoid organs but it cannot be detected in feather pulp.CVI-LTR reduced the load of oncogenic MDV DNA more efficiently than CVI988.